Admission blood pressure and 1‐year mortality in acute myocardial infarction. Issue 8 (6th February 2015) - Roth, D.; Van Tulder, R.; Heidinger, B.; Herkner, H.; Schreiber, W.; Havel, C.
Summary Aims Arterial hypertension is a well‐established factor for increased risk of cardiovascular diseases, but low admission blood pressure has also been suggested as predictor for increased mortality. We hypothesised that in patients with acute myocardial infarction admission blood pressure at the Emergency Department predicts long‐term mortality. Methods We included consecutive patients treated for acute myocardial infarction (AMI) at our 2, 200‐bed tertiary care hospital from 1991 to 2009 into our cohort. Systolic, diastolic and pulse pressure on admission were analysed as main predictors for 1‐year mortality. We adjusted for several baseline factors and tested for interactions using multivariable regression models. Results We included 3943 patients among whom 3604 were alive after 1 year. With increasing admission blood pressure 1‐year mortality risk decreased incrementally to a 70% reduced relative risk in the highest blood pressure categories vs. the lowest categories. This effect was independent of blood pressure modifying interventions. Conclusions In acute myocardial infarction, admission blood pressure predicts long‐term mortality in an inverse relation. With increasing admission blood pressure long‐term mortality decreases. Low admission blood pressure should serve as a warning sign in patients with AMI. Admission blood pressure should therefore be interpreted in opposite to the regular, preventive, point of view.